Effect of Protecting Agent Concentration, Catalyst (mol %) and Temperature on the Protection of 2-Propanol Catalyzed by Dodeca-Tungstophosphoric Acid - Tayebee, Reza; Cheravi, Fatemeh (Asian Journal of Chemistry, 2010)
Protection of various alcohols with carboxylic acids catalyzed by heteropolyacids is realized as an efficient method among different familiar reaction pathways. Herein, effective reaction parameters such as temperature, alcohol:protecting agent mole ratio and catalyst (mol %) were investigated on the acetylation and formylation of 2-propanol with acetic acid, formic acid and ethyl formate, as acetylating agents, in the presence of dodeca-tungstophosphoric acid, H3PW12O40. Findings showed that efficiency of the protection system was increased by enhancing temperature, using higher amounts of catalyst and increasing concentration of the protecting agent. Obviously, enhancing concentration of the protecting agent was more effective than elevation of temperature on the reaction progress.